THE COMPLETE CLINICAL RESPONSE IN RECTAL CARCINOMA AFTER CHEMO RADIATION: Rectal Carcinoma After Chemo Radiation - Manzoor, Ammara; Haider, Ghulam; Zahoor, Saima; Bai, Ravisha; Khan, Muhammad Ejaz; Ahmad, Maqbool (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the complete clinical response in rectal carcinoma after neoadjuvant chemo radiation.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted in Clinical Oncology department, Jinnah PostgraduateMedical Centre Karachi, from Jan 2016 to Jan 2017.Material and Methods: Seventy Two Patients meeting the inclusion criteria were enrolled in study after completestaging workup. Neoadjuvant concurrent chemoradiotherapy was planned, consisting of oral capecitabine825mg/m2 BID five days a week along with 50.4 Gy Radiotherapy with linac machine. Radiation was deliveredover a period of 5 weeks at a rate of 1.8 Gy/day. Patients received Radiotherapy in Atomic Energy MedicalCentre (AEMC) and in Sindh Institute Urology & Transplant (SIUT), Radiation department. Chemotherapy wasgiven in clinical oncology department of JPMC. Sixty one patients completed planned treatment and wereavailable for post concomitant chemo radiotherapy response assessment with Pelvic CT/MRI after 6-8 weeks ofcompletion of concomitant chemo radiotherapy. Response assessment was done according to Response EvaluationCriteria in solid tumor (RECIST) criteria version 1.1 and then Patients were referred for surgical evaluation.Result: A total of 61 cases of locally advanced adenocarcinoma rectal cancer patients were included in the study.Mean age of the patients was 41 years with ± 17.06 years SD. Complete clinical response was identified in 4 (6.6%)while 31 (50.8%) were identified as partial response, progressive disease was 13 (21.3%) and 13 (21.3%) were withstable disease. All confounding variables were found statistically significant with p-value found less than 0.05.Conclusion: Neo-adjuvant chemoradiotherapy for locally advanced rectal cancer is associated with high rates oftumor response in terms of downs tagging (complete & partial) and is relatively safe with acceptable morbidity,which favors its use in future.